Menyelami Dampak Likuiditas, Leverage, dan Pertumbuhan Bisnis dalam Krisis Keuangan - Mariani, Sara (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2024)
Financial crises often have a significant impact on various aspects of a business, including liquidity, leverage and growth. Understanding how these three factors are interrelated and contribute to company dynamics during a financial crisis is important for making the right decisions. This research aims to explore the impact of liquidity, leverage and business growth in the context of the financial crisis, as well as to identify effective strategies in facing emerging challenges. This research approach is descriptive analysis, using historical data and case studies from various companies that have experienced previous financial crises. Data will be analyzed quantitatively and qualitatively to understand the relationship between liquidity, leverage, growth and the company's response to the crisis. The research results show that liquidity, leverage, and growth have a complex and interrelated role in influencing company performance during the financial crisis. Effective strategies include good risk management, diversification of funding sources, and a focus on operational efficiency.